Social perceptions and attitudes towards climate change in Poland and in Turkey - Anna Dubel; Kaan Bas (Economic and Environmental Studies (E&ES), 2017)
Climate change is perceived as a threat to future human well-being and a challenge to sustainable development of local communities and economies world-wide. While some countries and regions are expected to experience slight gains from the climatic changes the other are exposed to major losses. Ever more frequent natural disasters come as warning symptoms of the changes. However, for the sake of effective and efficient adaptation in various world regions answers to the following questions are important: do people notice this changes, do they experience their negative effects, are they satisfied with the climate change mitigation and adaptation actions taken by the governments, are they willing to participate to contribute to these actions. The perceptions and attitudes towards these issues are important factors in effective and efficient implementation of climate policies. In order to contribute to this important goal a research was designed to elicit people's perceptions of and attitudes towards climate change as well as related mitigation and adaptation policies in Poland and in Turkey. These two countries were chosen to cover the variety of climate conditions. The aim of the paper is to present and analyse the outcomes collected from the conducted national Internet surveys (N=156) on perceptions of climate change as well as social expectations regarding climate change solutions in both countries. Analysis of the survey results help to understand the problems and social needs related to climate change. The results were confronted with the state-of-the-art scientific literature as well as strategic policy documents and their evaluations' reports to discuss the policy relevance of the findings and conclusions.
Keywords: D71; D78; Q54; 330; issues; needs; climate change; Poland; Turkey